5 giraffes - Dagg, Anne Innis (Fitzhenry & Whiteside, 2016)
"The latest in the 5 Animals series, with an introduction by Rob Laidlaw, 5 Giraffes profiles five unique giraffes from both captivity and the wild. Accompanying the five giraffe profiles is information on their diet, social life, and chapters on some of their more unique aspects, like the giraffe's unusual body. Includes full color photographs throughout, glossary, bibliography, table of contents and index." -- Amazon.com